2022
DOI: 10.3389/fgwh.2021.807817
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Objectively Assessed Sleep and Depressive Symptoms During Pregnancy and Post-partum

Abstract: IntroductionSleep problems are common in pregnancy but many studies have relied only on self-reported sleep measures. We studied the association between objectively measured sleep and peripartum depressive symptoms in pregnant women.Material and MethodsSleep was assessed using Actiwatch accelerometers in a sample of 163 pregnant women in the late first (weeks 11–15) or early second trimester (weeks 16–19). Depressive symptoms were assessed in gestational weeks 17, 32 and at 6 weeks post-partum using the Edinbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
1
0
4
Order By: Relevance
“…Menurut penelitian Pitsillos et al, (2021) gangguan tidur dianggap sebagai salah satu gejala paling menonjol pada pasien depresi. Gangguan tidur merupakan faktor risiko munculnya depresi, tetapi juga merupakan prediktor depresi.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Menurut penelitian Pitsillos et al, (2021) gangguan tidur dianggap sebagai salah satu gejala paling menonjol pada pasien depresi. Gangguan tidur merupakan faktor risiko munculnya depresi, tetapi juga merupakan prediktor depresi.…”
Section: Discussionunclassified
“…Gangguan tidur yang umum terkait dengan depresi adalah latensi tidur yang berkepanjangan, susah untuk mempertahankan tidur, dan menyebabkan kurangnya waktu tidur total. Dalam kehamilan, masalah gangguan tidur memainkan peran utama dalam perkembangan depresi pada maternal (Pitsillos et al, 2021).Hasil studi terbaru oleh Bao et al (2022) menyatakan bahwa gangguan tidur selama hamil dikaitkan dengan faktor sosial, psikologis, dan fisiologis. Ditemukan bahwa banyak faktor yang menyebabkan gangguan tidur seperti usia, paritas, pendapatan, pendidikan, dukungan keluarga dan dukungan sosial.…”
Section: Discussionunclassified
“…Nėštumas ir laikotarpis po gimdymo susiję su padidėjusia psichikos sveikatos problemų atsiradimo rizika moterims [1]. Pogimdyminė depresija (PD) yra viena iš labiausiai paplitusių nėštumo ir gimdymo komplikacijų [2].…”
Section: įVadasunclassified
“…Šis sutrikimas paveikia 10 -15 proc. vaisingo amžiaus pasaulio moterų [1]. Depresijai po gimdymo būdingi tokie simptomai kaip liūdesys, beviltiškumas, susidomėjimo ar malonumo jausmo praradimas kasdienėse veiklose, padidėjęs verksmingumas, dirglumas, nerimas, nuovargis, kaltės jausmas, miego, apetito bei svorio pokyčiai, dėmesio koncentracijos sumažėjimas, nesugebėjimas pasirūpinti savimi ar kūdikiu, mintys, susijusios su savižala ar savižudybe [2][3][4].…”
Section: įVadasunclassified
“…In addition, physical activity [20], depression [21][22] and social support [23] are associated with sleep during pregnancy. A large, multi-ethnic survey found that social capital was signi cantly associated with adult sleep [24].…”
Section: Introductionmentioning
confidence: 99%